Micro- and Macrocirculatory Changes During Sepsis and Septic Shock in a Rat Model. Issue 5 (May 2018) - Hua, Tianfeng; Wu, Xiaobo; Wang, Wei; Li, Hao; Bradley, Jennifer; Peberdy, Mary A.; Ornato, Joseph P.; Tang, Wanchun
Abstract : ABSTRACT: Microcirculation is the motor of sepsis. In the present study, we investigated whether microcirculatory alterations occur before changes of systemic hemodynamics in a rat model of cecum ligation and puncture (CLP)-induced sepsis. We further investigated renal microcirculatory changes during sepsis and compared those with buccal microcirculation. Twelve male Sprague-Dawley rats were randomized into a sham control group (n = 6) and a CLP group (n = 6). Perfused microvessel density (PVD) and microvascular flow index (MFI) were evaluated using sidestream dark field (SDF) video microscopy at baseline—60, 120, 180, 240, 300, and 360 min following CLP. A semiquantitative score was calculated for vessels of less than 20 μm, primarily representing the capillaries. Hemodynamic measurements such as cardiac output (CO), aortic pressure (AP), heart rate (HR), end-tidal CO2 (ETCO2 ), blood pH, and lactate were measured simultaneously. The serum cytokine interleukin 6 (IL-6) was measured at baseline—120, 240, and 360 min. In the CLP group, buccal PVD and MFI were reduced at 180 min ( P  < 0.05 vs. baseline); renal PVD and MFI were reduced at 180 min ( P  < 0.05 vs. baseline), but MAP and CO did not change until 300 min after CLP. In the rat model of peritonitis-induced sepsis, microcirculatory alterations of both peripheral mucosa and kidney occurred earlier than global hemodynamics. Monitoring the microcirculation may provide a means of early detection of circulatory failure during sepsis. The changes of renal microcirculation correlate with that of buccal during sepsis and septic shock.